2021
DOI: 10.1021/acsapm.1c00176
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-Free Superhydrophobic Surface by Single-Step-Synthesized Homogeneous Polymeric Raspberry Nanoparticle Coating

Abstract: We introduce a superhydrophobic surface that is composed of homogeneous polystyrene (PS) raspberry nanoparticles of around 50 nm diameter, via a convenient single-step scalable synthesis method. The surface has multiple stabilization wetting points, which is caused by hierarchical roughness from the unique raspberry morphology. Raspberry morphology also enables PS (which has higher surface tension than fluorinated materials) to have superhydrophobicity with more than 120°of the receding contact angle as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(43 reference statements)
2
4
0
Order By: Relevance
“…Decrease in RCA values as well as the Cassie–Baxter to Wenzel transition owing to abrasion has recently been reported in the literature for polystyrene NP surfaces, wherein recovery of superhydrophobicity was achieved by repetitive spray coating of the NPs. 11 In our case, exposing the underlying surfaces after abrasion also appears to result in an analogous result, wherein the superhydrophobicity of the sample is retained. ACA and RCA goniometry images after different mechanical testing steps ( Figure S20 ), as well as additional movies of contact angle measurements after peel 1 (see Movie S9 ), after peel 5 (see Movie S10 ), after abrasion 1 (see Movie S11 ), and after abrasion 2 (see Movie S12 ), are available in the Supporting Information.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Decrease in RCA values as well as the Cassie–Baxter to Wenzel transition owing to abrasion has recently been reported in the literature for polystyrene NP surfaces, wherein recovery of superhydrophobicity was achieved by repetitive spray coating of the NPs. 11 In our case, exposing the underlying surfaces after abrasion also appears to result in an analogous result, wherein the superhydrophobicity of the sample is retained. ACA and RCA goniometry images after different mechanical testing steps ( Figure S20 ), as well as additional movies of contact angle measurements after peel 1 (see Movie S9 ), after peel 5 (see Movie S10 ), after abrasion 1 (see Movie S11 ), and after abrasion 2 (see Movie S12 ), are available in the Supporting Information.…”
Section: Resultssupporting
confidence: 57%
“…Generally, developing such surface features can be easier with polymers than with inorganic materials like metals, which often require energy-intensive and/or complex techniques such as laser ablation, chemical etching, and lithography. This difference makes polymers an attractive material choice to develop textured or patterned superhydrophobic materials, both with and without NPs. Several techniques including, but not limited to, spray coating, solvent-assisted phase separation, and photopolymerization-based patterning , have been reported in the literature to develop excellent polymeric superhydrophobic surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The WCA of PS is 117.3°, higher than previous reported 91.3°. [44] A gradual decrease of WCA was seen after introducing SiO 2 nanoparticles in composite with a concentration of 10 wt % (108.4°) and 30 wt % (100.8°). This could indicate that combining effects of hydrophobic properties of PS and the morphological change after adding SiO 2 together determines the WCA of PS/SiO 2 composite film.…”
Section: Pmma-sio 2 and Ps-sio 2 Encapsulationmentioning
confidence: 94%
“…PS is a promising polymer for encapsulation in different applications. [42][43][44] It was previously found that PS film coated from spin coating exhibited high compactness, and PS encapsulated PSCs showed remarkable humidity stability. [43] In order to obtain superhydrophobic properties for PS, Kim et al [44] applied a convenient single-step scalable synthesis method to create hierarchical roughness.…”
Section: Pmma-sio 2 and Ps-sio 2 Encapsulationmentioning
confidence: 99%
See 1 more Smart Citation